Development of a Board Game to Enhance Learning Achievement in Quality Store Systems for Retail Store Management - Supornpraditchai, Tanya; Tansuwan, Kittibhop (Journal of Information and Learning [JIL], 2025)
The objectives of this study were to 1) create a board game to improve learning achievement in the quality store system (QSS) for retail store management, and 2) measure students' learning outcomes after playing the game. The study used a research and development (R&D) strategy, including design thinking, game-based learning (GBL), and the mechanics-dynamics-aesthetics (MDA) framework to create "MyShop," a board game that simulates product selection, staffing decisions, and quality store systems. Purposive sampling was used to identify 30 key informants working for a major convenience store chain, including 10 QSS executives, 10 operational workers, and 10 store managers who were chosen based on their knowledge, position in QSS implementation, and participation willingness. In addition, three specialists in instructional game design and retail management analyzed and improved the board game prototype. The sample group consisted of 278 first-year students from the Modern Trade Business Management Program chosen at random using cluster sampling. The research instruments comprised 1) in-depth interviews and focus group questions examined using content analysis, 2) the "MyShop" board game prototype with cards (Situation, Product, Customer, Event, and QSS), tokens, and boards, and 3) a 35-item multiple-choice pretest and posttest. To assess changes in learning achievement, data from student assessments were evaluated with paired t-tests. The game is considered "very appropriate" by specialists, demonstrating its high quality and suitability for instructional usage. QSS knowledge improved significantly, with exam scores improving from 18.83 to 26.54 (p < .05). The game improved students' comprehension of QSS principles, including service, assortment, and value, while also encouraging interactive and practical learning. These findings show that combining GBL with MDA can result in immersive, effective educational tools. The "MyShop" board game is a unique way for students to learn retail management that encourages critical thinking, collaboration, and real-world application, making it useful for both academic and professional development.